Pengaruh Budaya Organisasi dan Kepemimpinan Terhadap Kinerja Pegawai Di Biro Advokasi, Sekretariat Jenderal, Kementrian Keuangan - Afrita Afrita; Bambang Nurakhim; Widya Nengsih (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
Digital transformation and increasing regulatory complexity compel government legal units, such as the Advocacy Bureau of the Secretariat General of the Ministry of Finance, to become more adaptive and innovative. This study aims to examine the impact of organizational culture and leadership on employee performance, both individually and simultaneously. A quantitative approach with an explanatory survey design was employed, involving the entire population of 99 employees through a saturated sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and then analyzed using multiple linear regression with SPSS 20.0. The results indicate that organizational culture and leadership have a significant positive effect on employee performance. A strong work culture and effective leadership create an environment that supports productivity and the achievement of organizational goals. Practically, this study emphasizes the importance of internalizing organizational values and developing transformational leadership styles as strategies to enhance performance. These findings contribute to the advancement of human resource management in the public sector and provide a foundation for policy interventions in bureaucratic reform within government legal units.